Analisis Kinerja Routing Protokol Multi-Copy dengan Menggunakan Management Buffer First In-First Out (FIFO) dan Most Forwarded First (MOFO) pada Delay Tolerant Network (DTN) - Riski Manta Simanjorang; Heru Nurwarsito (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
Delay Tolerant Network (DTN) is a network that uses a special architecture has been developed with effort to connect between devices that has high delay time used changing connection. Routing multi-copy is a routing that minimizing network delay and maximizing data transmission when compared to routing Single-Copy. However, the absence of buffer management causes ineffective use of buffers each node. First In-First Out (FIFO) and Most Forwarded First (MOFO) is buffer management that can manage buffers that existeach node. FIFO buffer management can manage buffers based on the time the packet was entered. Whereas MOFO buffer management manages buffers based on the number of packet forwarding. Based on routing performance testing, buffer management can optimize packet delivery on DTN. The simulation results show that the highest value of delivery probability is 0.4799 which is found in the management of FIFO buffer with buffer size of 12MB with Spray-and-Wait routing. The lowest overhead ratio value obtained is 14.4873 found in the MOFO buffer management with a buffer size of 12MB with Spray-and-Wait routing. The lowest latency average value is 2092.7180s found in Spray-and-Wait routing using FIFO buffer management with 5MB buffer size.